Realisation of Music Teacher's Complaint Act with Gender Perspective in Solo Song WhatsApp Group - Nurul Aini; Eny Maulita Purnama Sari; Ahmad Efendi (CV. Creative Tugu Pena, 2024)
This qualitative study applies a pragmatic approach that investigates the complaining speech act (CSA) used by male and female music teachers based on the substansion of the Solo Song Competition in WhatsApp Group. Data were collected from the utterances of 13 participants using note-taking. The results indicated several findings. First, male music teachers have the highest preference for using the expression of disapproval with annoyance in the substance of after TM. In contrast, female music teachers have the highest preference for using the hint and the blame with explicit blame for person in the substance of before TM. The reason is not only about a high pressure from the school, parents, and students regarding the competitions, but also about dissatisfaction, dislike, and worry with a situation that is perceived as unfair, unprofessional, or harmful. Third, based on the comparison of the result of this study and previous researches reveals that gender influenced the choice of CSA usage. The results revealed that most of the complaints were related to issues regarding the competition regulations after TM. The competition regulations that were highly complained by both male and female music teachers were the inappropriate music instruments for men and women. The results also indicated that most of the complaints were addressed to the coordinator of the competition committee. The complaints submitted were a result of the untrustworthiness of male and female music teachers to the competition committee